Cryptic diversity of Crocidura shrews in the savannahs of Eastern and Southern Africa - (:unkn) unknown (My University, 2023)
Crocidura (Eulipotyphla, Soricidae) is the most species-rich genus among mammals, with high cryptic diversity and complicated taxonomy. The hirta-flavescens group of Crocidura represents the most abundant and widespread shrews in savannahs of eastern and southern Africa, making them a suitable phylogeographical model for assessing the role of paleoclimatic changes on current biodiversity in open African habitats. We present the first comprehensive study on the phylogeography, evolutionary history, geographical distribution, systematics, and taxonomy of the group, using the integration of mitochondrial, genome-wide (ddRAD sequencing), morphological and morphometrical data collected from specimens over most of the known geographic distribution. Our genomic data confirmed the monophyly of this group and its sister relationship with the olivieri group of Crocidura. There is a substantial genetic variation within the hirta-flavescens group, with three highly supported clades showing parapatric distribution and which can be distinguished morphologically: C. hirta, distributed in both the Zambezian and Somali-Masai bioregions, C. flavescens, known from South Africa and south-western Zambia, and C. cf. flavescens, which is known to occur only in central and western Tanzania. Morphometric data revealed relatively minor differences between C. hirta and C. cf. flavescens, but they differ in the colouration of the pelage. Diversification of the hirta-flavescens group has most likely happened during phases of grassland expansion and contraction during Plio-Pleistocene climatic cycles. Eastern African Rift system, rivers, and the distinctiveness of Zambezian and Somali-Masai bioregions seem to have also shaped the pattern of their diversity, which is very similar to sympatric rodent species living in open habitats. Finally, we review the group's taxonomy and propose to revalidate C. bloyeti, currently a synonym of C. hirta, including the specimens treated as C. cf.
Keywords: African Research